PENGGUNAAN METODE DRILL DALAM PELAKSANAAN PEMBELAJARAN MUSIK DAERAH DI SMP N 18 PADANG - Silvia Merlin; Syeilendra Syeilendra; Erfan Erfan (SENDRATASIK UNP, 2017)
AbstractThis research aims to describe the use of drilling method in teaching local music for 7th grade studens at SMP 8 Padang. Each learning activity consists of three meetings. The instruments of this research were the researcher herself as the observer, interview guidance and documents. The type of this research is qualitative research. The object were all students in class VII-1. The data were collected and analyzed based on the problem of the research. The research result shows that drilling method used in Cakdindin song has a significant effect toward improving the student’s ability. The learning activities were done in several phases in order to train the students and show a good learning result. Drilling method can give a new learning experience and can improve the student’s ability. Keywords: Drilling Method, Talempong Pacik, Cakdindin